Research on Digital Human Marketing Strategy - Guan, Xiuzhen (Innovative Applications of AI, 2025)
Abstract This paper focuses on the digital human marketing strategy, constructs a research framework with "technology-driven-content production-platform operation-ethical compliance" as the core, and systematically analyzes the application modes of large model semantic generation, multimodal interaction, templated content construction and personalized distribution mechanism in practice. Through in-depth analysis of typical cases such as JD Cloud Yanxi and Melatonin Virtual IP Renewal, the significant value of digital people in reducing costs and increasing efficiency, enhancing user engagement and achieving brand rejuvenation has been verified. The research points out that the coordinated development of technology, content and ethics will become a key factor in the success of digital human marketing. In the future, the focus should be on promoting the construction of emotional interaction capabilities and the integration of UGC ecology. This article can provide theoretical support and practical reference for enterprises to formulate sustainable digital human application strategies.